Product Development of Ice Cream Fiber-Fortified from Pomelo Puree - Kanjanarong, Jurupat; Plongbunjong, Vijitra (RMUTP Research Journal Sciences and Technology, 2024)
Development of fiber-fortified ice cream product from pomelo puree with a stabilizer in 4 recipes of 5, 7, 10 and 15 % was demonstrated. The results showed that the overrun and viscosity value of ice cream increased whereas the melting rate significantly decreased depended on pomelo content. Ice cream without pomelo puree remained the highest in sensory acceptance, and with the addition of pomelo puree, overall acceptance decreased. The ice cream formula with 7% pomelo puree was the highest overall acceptance (6.28±1.88), with no statistically significant difference from the standard formula without pomelo puree added. Overrun was 41.15±0.59%, the viscosity was 698.02±5.56 cps, and melting rate at 30 minutes was 22.23±0.24%. In addition, chemical analysis of 7% pomelo puree ice cream found that total soluble solids was 25.28±1.88 °Brix, pH was 3.35±0.30, and moisture and fiber content were 71.72 and 7.73 percent respectively when compared to a controlled ice cream using a commercial substance (CREMODAN® SE 709-M; Danisco Thailand Co., Ltd.) as a stabilizer, it was found that pomelo puree -infused ice cream had significantly higher fiber content (p ≤ 0.05). Also, the storage of pomelo ice cream at -20 °c for 12 days showed a lower total number of microorganisms and coliform bacteria than a standard criterion of the Ministry of Public Health.